HiperFer, a reduced activation ferritic steel tested for nuclear fusion applications. (December 2018) - Möller, S.; Kuhn, B.; Rayaprolu, R.; Heuer, S.; Rasinski, M.; Kreter, A.
Highlights: New reduced activation ferritic steel investigated for nuclear fusion applications. PSI-2 D2 plasma exposures up to 1150 K and modelling investigations. ppm level of D retention and W enrichment after exposure. Low impurity and C contents lead to low long-term activity. Component modelling shows at least 1.5 MW/m² load limit. Abstract: Materials are the most urgent issue in nuclear fusion research. Besides tungsten, steels are considered for unifying functional and structural materials due to their cost and mechanical advantages over tungsten. However, the fusion neutrons impose a strong constraint on the ingredients of the steel in order to avoid long lasting activation, while the material has to pertain sputtering resistance, low hydrogen retention, and long-term mechanical stability. In this proof-of-principle, we demonstrate the interesting properties of the new material HiperFer (High performance Ferrite) as a material suitable for fusion applications. The investigation covers neutron activation modelled by FISPACT-II, plasma sputtering and deuterium retention experiments in PSI-2, thermo-mechanical properties and component modelling. The material was found to feature a low nuclear inventory. Its sputtering yield reduces due to preferential sputtering by a factor 4 over the PSI-2 D2 plasma exposure with possible reductions of up to 70 indicated by SD.Trim.SP5 modelling. The exposure temperature shows a strong influence on this reduction due to metal diffusion, affecting layers of 1 µm in PSI-2 at 1150 K exposure for 4 h. Deuterium retention in the ppm range was found under all conditions, together with ∼10 ppm C and N solubility of the ferritic material. The creep and cyclic fatigue resistance exceed the values of Eu-97 steel. As an all HiperFer component, heat loads in the order of 1.5 MW/m² could be tolerated using water-cooled monoblocks. In conclusion, the material solves several contradictions present with alternative reduced-activation steels, but its applications temperatures >820 K also introduce new engineering challenges.